An Econometric Model of the Dependence of Economic Growth of GDP on a Group of Factors - Ismayilov, Vilayat; Ibrahimli, Chingiz; Yusifov, Elshad; Nasirova, Ofelya; Kamran, Shykhyly (Journal of Ecohumanism, 2025)
Purpose: The purpose of the study is to summarize the theoretical results on economic growth and build a model of the relationship between economic growth of GDP and other factors. Theoretical basis: The conducted research reflects the change in various points of view of researchers explaining the relationship between economic growth and a number of groups of factors. Research theories Economic growth is a complex phenomenon and theories must take into account natural resources, political institutions, etc. through a variety of factors. Method: The methodology of the study is based on research on economic growth, employment, credit investment, nominal incomes of the population, budgetary and internal expenses for work and research. Data collection was carried out with the help of statistical materials from EU countries and Azerbaijan. The systematic method is used to analyze materials that ensure an increase in the country’s GDP, employment, income, etc. Also, the calculation of the relationship of these indicators is carried out and refers to the country’s policy in the context of combating unemployment. Results and discussion: The results reveal that 188 countries produce a small portion of global GDP. Based on the analysis of the EU countries with the highest real GDP growth rate, it was noted that the economic growth of each year does not correspond to the previous values. An econometric model of the relationship between economic growth of GDP and groups of factors selected for the study is constructed. Note that the model justifies itself in determining the dependence of GDP in any country on multinational factors. The model allows us to determine the form of impact reflecting the dependence of economic growth of GDP and groups of factors in any period. Research results: The results of the study can be applied in determining priority areas for the economy and maintaining its pace at an optimal level of the national economy. Originality/value: The research contributes to the development of the country’s economy, thanks to the theoretical and practical results obtained. The relevance and value of the study are confirmed by the impact on the field of economics and the standard of living of the population.